Anticoagulation in atrial fibrillation with factor X deficiency—A management dilemma. Issue 9 (22nd July 2018) - Tan, Jian Liang; Loh, Kah Poh; Fortuna, Danielle; Ghaneie, Arezoo
Key Clinical Message: Factor X (FX) deficiency is a rare bleeding disorder. There is currently no clear guideline or recommendation for the appropriate selection of anticoagulation and management of patients with FX deficiency who require anticoagulation. We shared our experience in managing such patient, and we further discussed other possible treatment options. Abstract : Factor X (FX) deficiency is a rare bleeding disorder. There is currently no clear guideline or recommendation for the appropriate selection of anticoagulation and management of patients with FX deficiency who require anticoagulation. We shared our experience in managing such patient, and we further discussed other possible treatment options.